2019
DOI: 10.1111/bcpt.13207
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant potential of selegiline in treating acute toxicity of aluminium phosphide in rats

Abstract: Aluminium phosphide (AlP) is a highly toxic substance with a high mortality rate and no effective antidote. Once exposed to the moisture and acidic conditions of the stomach, AlP releases toxic phosphine (PH3) gas, which results in severe toxicity in poisoned subjects. Selegiline is a monoamine oxidase inhibitor with antioxidant and anti‐apoptotic properties, which is mostly prescribed for the treatment of mood disorders and Parkinson's disease. Since AlP has detrimental effects on cardiac physiology and mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The diagnosis of ALP poisoning is usually based on clinical suspicions; however, silver nitrate testing on stomach contents or breathing vapors is also used to confirm the diagnosis [11]. ALP poisoning presents no specific antidote; however, previous studies have suggested some treatment approaches, such as gastric lavage with sodium bicarbonate and the ingestion of charcoal [12]. Additionally, some specific treatment methods of ALP poisoning have been suggested, including the intravenous administration of magnesium sulfate, sodium bicarbonate, N-acetyl cysteine, digoxin, vasopressor, vitamin C, and vitamin E [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of ALP poisoning is usually based on clinical suspicions; however, silver nitrate testing on stomach contents or breathing vapors is also used to confirm the diagnosis [11]. ALP poisoning presents no specific antidote; however, previous studies have suggested some treatment approaches, such as gastric lavage with sodium bicarbonate and the ingestion of charcoal [12]. Additionally, some specific treatment methods of ALP poisoning have been suggested, including the intravenous administration of magnesium sulfate, sodium bicarbonate, N-acetyl cysteine, digoxin, vasopressor, vitamin C, and vitamin E [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Based on MDA content assessment in different animal and human samples, it has been shown that AlP significantly elevates levels of LPO. Moreover, AlP can increase ROS levels through disruption in the electron transfer chain and results to free radicals’ overproduction along with a disturbance in the antioxidant systems 30 31 32 . Antioxidant agents are the most important defense system of human body to fight free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in mortality has been seen with gastric lavage with potassium permanganate and mineral or coconut oil [9]. Other articles spoke favorably about other antidotes, including triiodothyronine, acetyl-L-carnitine, glutathione, liothyronine, milrinone, Laurus nobilis L, vasopressin, sodium selenite, sulfate, N-acetylcysteine, 6-aminonicotinamide, boric acid, melatonin, vitamins C and E [10], selegiline [11], and whole blood transfusion [12]. Other articles reviewed the roles of digoxin [13], extracorporeal cardiopulmonary resuscitation [14], aortic balloon [15], and prophylactic amiodarone for symptomatic improvement in cardiac function [16].…”
Section: Discussionmentioning
confidence: 99%